Information on Two USSR Botanical Conferences. - Dorogostayakaya, Ye V. (1961)
The Vegetation Laboratory of the far Northern- USSR Botanical Institute called a conference on 25-27 April 1960,- in the Botanical Institute imeni V. L. Komarov (BIN) of the USSR Academy of Sciences (AN USSR), dealing with the problems of vegetation and soils investigation in the Far North. Opening the conference, B. A. Tikhomirov (BIN) called attention to the great services-performed by the late B. N. Gorodkov in studying the processes of nature on the northern borders of our Notherland. The founder of Soviet tundra knowledge, B. N. Gorodkov was both a theoretician and a practicioner with an extremely varied approach to the tundra, a botanist, a physical geographer, a soil scientist, and an animal ecologist. Long ago, Gorddkov pointed out the necessity of making a complex study of tundra biogeocenozoics, i.e., of developing that trend which has now become a component part of tundra knowledge. Gorodkov first conceived the work which was carried out, and is being carried out, by his students and followers. It would be difficult to name any branch of Soviet knowledge on the tundra which has not been touched by the work of Gorodkov, which is also widely known abroad. The Conference, which was held in theBiN, was devoted to accomplishing a great deal of work, and this was entirely in-accord with the spirit of the great toiler for Soviet tundra knowledge, B. N. Gorddkov.